Factores asociados en la prevalencia de las infecciones respiratorias agudas en menores de 5 años atendidos en el Hospital General Guasmo Sur periodo junio - octubre 2023. - Rodríguez Cerezo, Yulisa Yamilex (2023)
Acute respiratory infection Acute respiratory infection is defined as the set of infections of the respiratory system caused by viral, bacterial and other microorganisms, with a period of less than 15 days, with the presence of one or more symptoms or clinical signs such as: cough, runny nose , nasal obstruction, sore throat, otalgia, hoarseness, noisy breathing, respiratory distress, which may or may not be accompanied by fever; Acute respiratory infection is the leading cause of morbidity and mortality in our environment, as well as consultation with health services and hospitalization in children under five years of age. the child develops between three to seven upper respiratory tract infections each year, which, depending on the intensity and compromise of the general state, can be mild, moderate or severe, the latter being responsible for significant mortality in infants and children under five years Objective: To determine the factors associated with the prevalence of acute respiratory infections in children under 5 years of age treated at the General Hospital Guasmo Sur. Period June - October 2023.Metology: Analysis - synthesis method: This method will be present in the ongoing research when the different investigations similar to our topic are analyzed, such as scientific journals and related documents. All this information must be synthesized to be used as a scientific basis.